THE HERITAGE OF THE LIBRARY OF THE NESVIZH RADZIWILLS IN LITHUANIA - NARBUTIENĖ, DAIVA (Knygotyra, 2015)
The Radziwills, an aristocratic family of the Great Duchy of Lithuania, amassed sizable book collections at their estates. Notable is the Nesvizh castle collection, started in the middle of the XVI century by the Great Chancellor of Lithuania, Mikalojus Radvila (Radziwill) the Black. In 1772, after the first division of the Republic of the Two Nations, this collection – one of the state’s largest personal libraries – was removed to the Russian Academy of Sciences in St. Petersburg. The interest in the cultural heritage of the Nesvizh Radziwills in Lithuania was prompted by the iniciative of the cultural institutions of neighbour countries (Poland, Bielorussia and, to a certain degree, Russia) to study the heritage of the Nesvizh Radziwills, dispersed throughout various countries. The last year, the virtual reconstruction of the Radziwills’ collection in Nesvizh was a subject of international scientific conferences and meetings, and of an international pilot project. In Lithuanian libraries, there are several remaining copies with the ex-librises of the Nesvizh Radziwills: three in the Library of the Lithuanian Academy of Sciences, one each in the libraries of Vilnius University, of the Kaunas University of Technology and of the Kazys Varnelis house-museum. The electronic catalogue of the Nesvizh Radziwills’ library, compiled in the Karol Estreicher Institute of Polish Bibliography, includes, among others, a copy from the Library of the Lithuanian Academy of Sciences.